2019
DOI: 10.1051/0004-6361/201834126
|View full text |Cite
|
Sign up to set email alerts
|

The bimodal [Mg/Fe] versus [Fe/H] bulge sequence as revealed by APOGEE DR14

Abstract: Context. The Galactic bulge has a bimodal metallicity distribution function: different kinematic, spatial, and, potentially, age distributions characterize the metal-poor and metal-rich components. Despite this observed dichotomy, which argues for different formation channels for those stars, the distribution of bulge stars in the α-abundance versus metallicity plane has been found so far to be a rather smooth single sequence. Aims. We use data from the fourteenth data release of the APOGEE spectroscopic surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…Bensby et al (2013Bensby et al ( , 2017 studied the abundance distribution of bulge stars using microlensed dwarfs and subgiants within 1 kpc of the Galactic center. They found that ([Fe/H], [α/Fe]) distribution of stars in the Galactic bulge are very similar to the sequence found in the inner disc (see also Rojas-Arriagada et al 2019) . This is correctly predicted by our model.…”
Section: Relation To Other Studiesmentioning
confidence: 55%
“…Bensby et al (2013Bensby et al ( , 2017 studied the abundance distribution of bulge stars using microlensed dwarfs and subgiants within 1 kpc of the Galactic center. They found that ([Fe/H], [α/Fe]) distribution of stars in the Galactic bulge are very similar to the sequence found in the inner disc (see also Rojas-Arriagada et al 2019) . This is correctly predicted by our model.…”
Section: Relation To Other Studiesmentioning
confidence: 55%
“…In contrast to Rojas-Arriagada et al (2019), however, the two blobs define completely detached sequences, without merging, thus showing a true chemical discontinuity. The new maps show that the chemical discontinuity seen in the solar neighborhood bin (mostly studied also by other surveys -middle row, 4th column), extends towards the Bulge, and become completely separated, being very similar to what was found by Fuhrmann (1998Fuhrmann ( , 2011 within 25 pc but now extended to larger metallicities (as expected given the observed abundance gradients in the galactic disc).…”
Section: For Discussion)mentioning
confidence: 91%
“…We adopt the stellar parameters and abundances from the APOGEE DR16 catalogue, and spectro-photometric distances with the procedure described in Rojas-Arriagada et al (2017). Since the magnesium abundance has been shown to be the most reliably measured α-element in the APOGEE survey (Rojas-Arriagada et al 2019;Jönsson et al in (Pinsonneault et al 2018). Note that the ages of stars become less reliable at [Fe/H]< −0.5, owing to the lack of training set stars and the effects of extra-mixing at these metallicities (Mackereth et al 2019).…”
Section: Datamentioning
confidence: 99%